Newsgames : journalism at play. - Bogost, Ian, ....-; Ferrari, Simon, ....-; Schweizer, Bobby, ....- (Cambridge : MIT, 2010)
Journalism has embraced digital media in its struggle to survive. But most online journalism just translates existing practices to the Web: stories are written and edited as they are for print; video and audio features are produced as they would be for television and radio. The authors of Newsgames propose a new way of doing good journalism: videogames. Videogames are native to computers rather than a digitized form of prior media. Games simulate how things work by constructing interactive models; journalism as game involves more than just revisiting old forms of news production. The book describes newsgames that can persuade, inform, and titillate; make information interactive; re-create a historical event; put news content into a puzzle; teach journalism; and build a community. Wired magazine's game Cutthroat Capitalism, for example, explains the economics of Somali piracy by putting the player in command of a pirate ship, offering choices for hostage negotiation strategies. And Powerful Robot's game September 12th offers a model for a short, quickly produced, and widely distributed editorial newsgame. Videogames do not offer a panacea for the ills of contemporary news organizations. But if the industry embraces them as a viable method of doing journalism--not just an occasional treat for online readers--newsgames can make a valuable contribution.